2013
DOI: 10.1186/1471-230x-13-136
|View full text |Cite
|
Sign up to set email alerts
|

The postoperative bleeding rate and its risk factors in patients on antithrombotic therapy who undergo gastric endoscopic submucosal dissection

Abstract: BackgroundThere is a lack of consensus regarding the risk of postoperative hemorrhage in patients on antithrombotic therapy who undergo endoscopic submucosal dissection (ESD).We examined postoperative bleeding rates and risk factors for postoperative hemorrhage from post-ESD gastric ulcers in patients on antithrombotic therapy.MethodsThe subjects of this study were 833 patients who underwent ESD of gastric tumors. Of these, 743 were not on antithrombotic therapy and 90 were on some form of antithrombotic thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 29 publications
3
98
4
2
Order By: Relevance
“…40 Gastroprotective agents were associated with lower PPB in patients undergoing AT in 1 study. 54 Corticosteroid use was not identified as a risk factor for PPB. 16,24,43 Lesion characteristics.…”
Section: Risk Factors For Ppbmentioning
confidence: 89%
“…40 Gastroprotective agents were associated with lower PPB in patients undergoing AT in 1 study. 54 Corticosteroid use was not identified as a risk factor for PPB. 16,24,43 Lesion characteristics.…”
Section: Risk Factors For Ppbmentioning
confidence: 89%
“…Direct oral anticoagulants (DOACs) target either thrombin or factor Xa, thereby attenuating thrombosis. Currently, 4 DOACs can be used for preventing stroke in atrial fibrillation: dabigatran, rivaroxaban, apixaban, and edoxaban; however, there is insufficient data concerning the management of patients taking anticoagulants who undergo ESD for EGC [19-23]. Therefore, we investigated the outcomes of ESD for EGC in patients taking anticoagulants, including the risk of bleeding during or after ESD.…”
Section: Introductionmentioning
confidence: 99%
“…There were also some unanswered questions regarding the bleeding of post-ESD and aspirin use. A recent study showed that the ratio of bleeding after ESD was higher in the anticoagulant agents group than in the nonanticoagulants agent group, 23.3% and 2%, respectively; however, the study did not examine the methods of drug use or which antithrombotic drugs may increase the rate of bleeding (27). In another study, the use of heparin caused a higher risk of delayed bleeding after gastric ESD (33).…”
Section: Discussionmentioning
confidence: 96%
“…In another study, the use of heparin caused a higher risk of delayed bleeding after gastric ESD (33). Takeuchi found that combining LDA with warfarin and longer ESD operations increased the rate of post-ESD bleeding (27). Moreover, Satoshi showed that taking thienopyridine derivatives with aspirin increased the hazard of bleeding after ESD, particularly in gastric ESD (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation